Meningkatkan Daya Saing dan Kesiapan Kerja Santri melalui Edutechnopreneurship Berbasis AI dengan Pendekatan Neurocoaching - Utami, Pertiwi; Khulsum, Umi; Purnamasari, Sinta Ayu; Basrowi, Basrowi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This community engagement program sought to strengthen the competitiveness and work readiness of 30 Islamic boarding school students through AI-based edutechnopreneurship supported by a neurocoaching approach. The program addressed key challenges faced by pesantren, including limited vocational skills, low digital literacy, and lack of entrepreneurial mindset among students. Activities included training in halal bakery production, AI-assisted digital marketing, and Sharia-compliant business bookkeeping, implemented through a Participatory Action Research (PAR) framework. The integration of hands-on practice and neurocoaching reinforced students' growth mindset, motivation, and entrepreneurial skills. Pre-post assessments revealed that 86.7% of participants achieved competency across technical, digital, and managerial domains, surpassing the initial target of 80%. Outcomes included enhanced vocational abilities in bakery production, improved digital marketing capacity through social media and e-commerce platforms, better understanding of Sharia financial recording, and the establishment of a small-scale bakery unit. This unit serves as a foundation for advancing pesantren-based economic empowerment and provides a sustainable business model for future replication in similar Islamic educational institutions.